1979
DOI: 10.1172/jci109291
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Duct Sodium Reabsorption in Deoxycorticosterone-Treated Rats

Abstract: A B S T R A C T In vitro studies of isolated, perfused, cortical collecting tubules have demonstrated that prior chronic deoxycorticosterone acetate (DOCA) treatment increases sodium reabsorption in this nephron segment, yet sodium balance in vivo is maintained. To evaluate the effect of chronic DOCA treatment on collecting duct sodium reabsorption in vivo, we compared fractional sodium delivery (FDNa%) out of the superficial late distal tubule with the fraction of sodium remaining at the base and the tip of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Furthermore, in wholekidney samples, there were significant increases in the protein abundance of two proximal Na transporters, NHE3 and NaPi-2 ( Table 2). Although these changes would predict increased proximal NaCl absorption, micropuncture studies have revealed that Na delivery to the early distal tubule is not decreased during aldosterone escape (11,12). These observations would suggest that any increases in proximal tubule reabsorption during aldosterone escape are compensated for by decreases in Na absorption in the loop of Henle.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, in wholekidney samples, there were significant increases in the protein abundance of two proximal Na transporters, NHE3 and NaPi-2 ( Table 2). Although these changes would predict increased proximal NaCl absorption, micropuncture studies have revealed that Na delivery to the early distal tubule is not decreased during aldosterone escape (11,12). These observations would suggest that any increases in proximal tubule reabsorption during aldosterone escape are compensated for by decreases in Na absorption in the loop of Henle.…”
Section: Figurementioning
confidence: 99%
“…13,25,26 This is associated with declining Na ϩ reabsorption in the distal nephron despite elevated levels of aldosterone and occurs independent of changes in GFR. 26,27 Indeed, early micropuncture measurements demonstrated increases in urine flow and Na ϩ delivery to the CD during escape. 26,27 Details about the specific site(s) along the distal nephron involved in decreased Na ϩ reabsorption during aldosterone escape and the exact transport proteins involved in this escape, though, largely remain obscure.…”
mentioning
confidence: 99%
“…In view of similar findings in other natriuretic conditions (8-10, 17, 23), it seems unlikely that medullary tonicity influenced reabsorption by this segment. In previous studies of segmental sodium transport during more massive volume expansion, we (10,17) and others (8,9,23) found net addition of sodium between the LDT of superficial nephrons and the papillary base, indicative of preferential inhibition of sodium reabsorption in juxtamedullary nephrons. Using pharmacologic manipulation of transport, we suggested that this inhibition was localized to the thin ascending limb of the LH (10).…”
Section: Discussionmentioning
confidence: 49%